REGARDING NATURAL AND ARTIFICIAL RADIOACTIVE BACKGROUND - Israilov M (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
the article describes natural and artificial radioactive background, their sources, background levels, its annual increase, its causes, nuclear reactions, biological effects, and in conclusion, appropriate conclusions are drawn.